Deletion of zmp1 improves Mycobacterium bovis BCG-mediated protection in a guinea pig model of tuberculosis. Issue 11 (10th March 2015) - Sander, Peter; Clark, Simon; Petrera, Agnese; Vilaplana, Cristina; Meuli, Michael; Selchow, Petra; Zelmer, Andrea; Mohanan, Deepa; Andreu, Nuria; Rayner, Emma; Dal Molin, Michael; Bancroft, Gregory J.; et al.
Highlights BCG zmp1 mutants confer increased protection in a guinea pig model of TB as compared to BCG. The improved protective efficacy of zmp1 deletion mutants is independent on the BCG sub-strain. BCG zmp1 deletion mutants demonstrate an improved safety profile in a SCID mouse model. BCG zmp1 mutants are promising candidates for further vaccine development due to their protective efficacy and safety profile.